Critiquing Psycho-social Abjection of Young Adult’s Body in Salinger’s The Catcher in the Rye - Thapa, Hukum (Bon Voyage, 2023)
This study applies Julia Kristeva and Karen Coats’ critical findings into the psychosocial abjection of the body to an analysis of J.D. Salinger’s The Catcher in the Rye. It makes an argument for how and why Holden Caulfield, the young adult protagonist of The Catcher in the Rye, experiences body abjection and what benefits from it. It argues that adolescents experience rejection as a part of their adult lives. It also makes the case that young adults degrade their own bodies in order to gain their freedom, individuality, and maturity, and that adults degrade the bodies of teenagers in order to maintain their power over them. The yearning for freedom, identity, and adulthood is sparked by the rejection of one’s body. This work paves the way for future investigations concerning rejection and the milieu of diverse continents and societies among young adults.